First record of Spirometra spp. eggs in fecal samples from Panthera onca in the Brazilian Pantanal: a One Health approach. - Raad, Paul [UNESP]; Alencar Junior, Flávio Paixão de; Pacheco, Richard de Campos; Bressan, Samuel Felipe; Lins, José Gabriel Gonçalves [UNESP]; Fornazari, Felipe [UNESP] (FapUNIFESP (SciELO), 2025)
This study examines the presence of gastrointestinal parasites in fecal samples from free-ranging jaguars (Panthera onca) in the Pantanal biome and assesses their potential as bioindicators of environmental health at the human-animal interface using a noninvasive approach. In 2024, ten fresh fecal samples were collected from the ground at Piuval Lodge in the northern Pantanal, state of Mato Grosso, Brazil. All samples were morphologically consistent with large felids, suggesting a high likelihood of originating from jaguars, based on field evidence. Coproparasitological analysis using sedimentation and flotation techniques identified Spirometra spp. eggs, with a positivity rate of 100%. Additionally, 20% of the samples tested positive for Toxocara spp. and one sample was positive for the genus Ancylostoma. This study highlights that jaguars (Panthera onca) are a potential bioindicator of environmental health and a sentinel species in the Pantanal, thus emphasizing the interaction between wildlife, domestic animals and human activities.